2022
DOI: 10.14738/assrj.94.12106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Oil Price, Exchange Rate and the Trade Performance of Quoted Industrial Sectors at the All Securities Market (Asem) in Nigeria

Abstract: The study examined the dynamic interaction among oil price, exchange rate and the trading performance of quoted industrial sectors at the Nigerian stock exchange market from 1980 to 2020 used in a Panel Vector Error Correction Mechanism (PVECM) framework. Data were sourced from BP Energy Review, Central Bank of Nigeria Statistical Bulletin and Annual report of the Nigerian Stock Exchange Market. Findings showed that long run relationships were established for oil price, exchange rate and the stock market perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study confirms the debilitating effects of oil price shock on exchange rate dynamics in Nigeria. Empirical studies that found the same results for net oil-exporting countries are Tian et al (2020), Nwosa (2020), Abdullah and Muhammad (2021); Igbinovia and Ogiemudia (2021); Li (2021); Touil and Merabet (2021); Das (2021) and Ajeigbe (2022). Interestingly, the effects of the monetary policy rate, trade balance and the price level on global oil price are negligible.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
See 1 more Smart Citation
“…This study confirms the debilitating effects of oil price shock on exchange rate dynamics in Nigeria. Empirical studies that found the same results for net oil-exporting countries are Tian et al (2020), Nwosa (2020), Abdullah and Muhammad (2021); Igbinovia and Ogiemudia (2021); Li (2021); Touil and Merabet (2021); Das (2021) and Ajeigbe (2022). Interestingly, the effects of the monetary policy rate, trade balance and the price level on global oil price are negligible.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
“…The empirical literature on the nexus between oil price dynamics and exchange rate behaviour is already proliferated with studies targeted at net oil exporters and net oil importers, while a few other studies combined panel of countries without recourse to the specificity of their trading status. The first category includes studies conducted by Abdullah and Muhammad (2021); Ajeigbe (2022); Das (2021); Igbinovia and Ogiemudia (2021); Li (2021); Nwosa (2020); Tian et al (2020); Touil and Merabet (2021); among others. For the second category, the studies of Baghestani and Toledo (2019); Vochozka et al (2020); Castro & Jimenez‐Rodrıguez, 2020; Allam et al 2020 are few of the recent studies while Baek (2020) combined a panel of net oil importers and net oil exporters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…examined the effect of the exchange rate shocks on ten (10) sectoral stock returns in Nigeria from 2007 to 2018; examined symmetric and asymmetric relationship between exchange rate and sectoral stock returns. The autoregressive distributed lag and nonlinear autoregressive distributed lag only financial service sector moves in an asymmetric fashion in the short and long period without taking account of structural breaks and with structural breaks, non of the sectorial stock returns were asymmetric Ajeigbe (2022). examined the dynamic interaction among oil price, exchange rate and the trading performance of quoted industrial sectors at the Nigerian stock exchange from 1980 to 2020 a panel vector error correction mechanism (PVECM) framework long run relationships were established for oil price, exchange rate and the stock market performance of the industrial sectors; a long run negative relationship among oil prices, exchange rate and the stock market performance of industrial sector Fapetu et al (2017).…”
mentioning
confidence: 99%